The approach for alcohol consumption control in live music car activities of a community in northeastern region - Thongsrikate, Ittipong (Disease Control Journal, 2021)
Live music cars are popular in northeastern Thailand. It is like a mobile sound stage that attracts children and young people to participate in activities. However, it gives a chance for these people to access to alcohol consumption. The purpose of this paper was to investigate approach for alcohol consumption control in live music car activities of a community in northeastern Thailand. The study employed a qualitative research method. Data were collected through in-depth interview conducted with ten community leaders, ten local people, and five live music car owners. Besides, participatory and non-participatory observations were employed. Obtained data were analyzed by using content analysis. Results of the study revealed that approach for alcohol consumption control in live music car activities of a community in northeastern Thailand contained 4 aspects: 1) family and community control 2) community leader control 3) live music owner control, and 4) participant control (educational institution and actives hosts). The purpose of these approach was to limit alcohol consumption and save people participating in the activities.